Progressive radiation-induced rectal injury: is there an opportunity to get out of a vicious circle? A clinical case - Tatyana E. Skvortsova; Inna A. Oganezova; Olga I. Medvedeva (Терапевтический архив, 2023)
Radiation therapy is one of the main treatment option for prostate cancer used either independently or as a component of combined and complex treatment of the disease. Modern achievements make it possible to deliver doses of radiation that match the exact dimensions of the tumor for greater efficacy, with minimal exposure of the surrounding tissues, however, does not eliminate them. In most patients, clinical manifestations of chronic radiation proctitis occur during the first 2 years after radiation therapy. The article summarizes the current knowledge about pathophysiology, clinical manifestations, diagnostics and treatment options for this condition. In this paper, we present a case of complicated of chronic radiation proctitis.